From a reflectrometry code to a 'standard' EC code to investigate the impact of the edge density fluctuations on the EC waves propagation. (18th September 2019) - Bertelli, N; Kramer, G J; Valeo, E J
Abstract: In this work we employ and extend a 2D/3D code (FWR2D/FWR3D), originally developed for reflectrometer simulations, to study the impact of the edge density fluctuations on the electron cyclotron (EC) wave beam propagation. 2D and 3D simulations for DIII-D-like plasma are discussed with and without the presence of the edge density fluctuations in order to evaluate the impact on the EC wave beam broadening at the location of the EC resonance. Moreover, a comparison between the paraxial and the full-wave solution (which are both implemented in the code, making it very flexible) of the EC beam with and without edge density fluctuations is shown. The paraxial solution is numerically convenient and in very good agreement with the full-wave solution. A scan in the amplitude of edge density fluctuations is performed together with an average with 1000 different fluctuations realizations. For the case shown in this work, an ensemble larger than 100 independent edge density fluctuations shows to reasonably represent the impact of the fluctuations on the EC beam. Our simulations shown here demonstrate the importance of the edge density fluctuations to the EC propagation in agreement with previous work.